2023
DOI: 10.1002/pc.27295
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene‐based nanocomposite with improved mechanical properties: Effect of cellulose nanofiber and polyrotaxane with partial miscibility

Abstract: The mechanical properties and miscibility of polymer‐based composites containing cellulose nanofiber (CNF) and polyrotaxane (p‐rtx) as organic fillers were studied in detail. CNF and p‐rtx were introduced as powders into a polypropylene (PP) matrix, and composites were prepared using a simple melt‐compounding method. The best mechanical properties were achieved when CNF and p‐rtx were loaded at a concentration of 0.6 wt%. The Young's modulus of the composite increased by 760 MPa compared with that of the PP ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…8 However, due to its inadequate impact performance and low modulus, the PP matrix is primarily combined with calcium carbonate (CaCO 3 ), clay, silica, or talc to improve its mechanical, thermal, and rheological properties. 9,10 In particular, talc, characterized by its layered structure of magnesium silicate, serves as both a reinforcement and a cost-saving element in PP composites while improving their toughness. 11 The reinforcing effect of talc could be notably observed up to 20 wt % loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, due to its inadequate impact performance and low modulus, the PP matrix is primarily combined with calcium carbonate (CaCO 3 ), clay, silica, or talc to improve its mechanical, thermal, and rheological properties. 9,10 In particular, talc, characterized by its layered structure of magnesium silicate, serves as both a reinforcement and a cost-saving element in PP composites while improving their toughness. 11 The reinforcing effect of talc could be notably observed up to 20 wt % loading.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the automotive sector has made pioneering innovations in environmental sustainability which involves optimizing material choices for lightweighting and durability. , The shift toward advanced materials for lightweight and high-strength characteristics has driven the adoption of polymer composites as alternatives to traditional metal parts, aligning with broader sustainability goals. Polypropylene (PP) is extensively employed as a polymer matrix in polymer composites due to its low density and cost, favorable processability, remarkable thermal stability and chemical resistance, and recyclability. , Additionally, PP shows great compatibility for reinforcement or blending with various polymeric materials or organic/inorganic additives . However, due to its inadequate impact performance and low modulus, the PP matrix is primarily combined with calcium carbonate (CaCO 3 ), clay, silica, or talc to improve its mechanical, thermal, and rheological properties. , In particular, talc, characterized by its layered structure of magnesium silicate, serves as both a reinforcement and a cost-saving element in PP composites while improving their toughness . The reinforcing effect of talc could be notably observed up to 20 wt % loading. , Guerrica-Echevarria et al proved the increased Young’s modulus, with nearly a 40% enhancement in modulus observed for each 10% increment in talc content, by using injection-molded PP composites containing 10, 20, and 40% talc .…”
Section: Introductionmentioning
confidence: 99%